The taxonomic reassessment of a reportedly extinct bat, Pipistrellus sturdeei (Chiroptera: Vespertilionidae) - Görföl, Tamás; Fukui, Dai; Csorba, Gábor (Zootaxa, 2020)
Insular bats are among the most vulnerable mammal species whose survival are threatened by several human-mediated factors, frequently paralleled by the paucity of information and lack of adequate management plans. Pipistrellus sturdeei is known only by the holotype collected from the remote Bonin Islands more than a hundred years ago and is declared to be extinct by the Japanese authorities. However, its taxonomic validity and collection locality is regarded ambiguous by some scholars. Here we report details about its collection circumstances and provide evidence that it morphologically differs from all other pipistrelles. We would like to raise attention on the species and the importance of a detailed study on its possible survival.